Diverse Targeted Approaches to Battle Multidrug Resistance in Cancer - Shankaraiah, Nagula; Nekkanti, Shalini; Ommi, Ojaswitha; P.S., Lakshmi S. (Current Medicinal Chemistry, 2019)
The efficacy of successful cancer therapies is frequently hindered by the development of drug resistance in the tumor. The term ‘drug resistance’ is used to illustrate the decreased effectiveness of a drug in curing a disease or alleviating the symptoms of the patient. This phenomenon helps tumors to survive the damage caused by a specific drug or group of drugs. In this context, studying the mechanisms of drug resistance and applying this information to design customized treatment regimens can improve therapeutic efficacy as well as the curative outcome. Over the years, numerous Multidrug Resistance (MDR) mechanisms have been recognized and tremendous effort has been put into developing agents to address them. The integration of data emerging from the elucidation of molecular and biochemical pathways and specific tumor-associated factors has shown tremendous promise within the oncology community for improving patient outcomes. In this review, we provide an overview of the utility of these molecular and biochemical signaling processes as well as tumor-associated factors associated with MDR, for the rational selection of cancer treatment strategies.
Keywords: Alternative kinase inhibitors